DIALECTAL VARIATION AND COMMUNICATIVE ACCOMMODATION AMONG BANGGAI AND GORONTALO STUDENTS IN A MULTICULTURAL CAMPUS CONTEXT - Syah Gita Agatha Nopallina; Dwi Mutmaina Pratiwi Talalu; Aulia Maulid Latangka; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines dialectal variation and communication strategies among Banggai and Gorontalo students at Universitas Negeri Gorontalo. Using a descriptive qualitative approach, data were collected through interviews and observations of students’ informal interactions. The findings show that dialectal differences appear in vocabulary choice, pronunciation, particles, forms of address, and intonation. These differences sometimes create misunderstanding, particularly when directness or high intonation is interpreted differently by students from another regional background. However, students also employ several communication strategies, including switching to Indonesian, clarifying meaning, adjusting tone, and using familiar expressions to maintain solidarity. The study suggests that dialectal variation in campus interaction is not merely a linguistic difference, but also a marker of identity, solidarity, and intercultural negotiation.